A Frequency and Semantic Analysis of the Most Frequent Connotations of the Notion of Beauty (European Journal of Behavioral Sciences, 2021)
In order to define and determine the meaning of a notion, its use in the natural language is a valuable source of information. Analyses aimed at understanding the meaning of a particular expression include the observation of its connotations. It is assumed that each meaningful word in a language is characterised by a set of semantic connotations and these connotations are a product of the experiences that are communicated by the use of the word. The term “beauty” is one of the most complex and multidimensional words. The study concentrates on the identification of its connotations in the natural language of 1,558 users aged 19 to 89 years (mean age = 45.23; SD = 16.33 years); there were slightly more women in the sample (52.7%). The most frequent connotation of the notion of beauty was nature, followed by woman, love, family, and child (the connotations occurred in more than 15 % of the language users in the observed sample). Most of the connotations (93.7 %) were nouns, which testifies to the substantive character of the notion of beauty. The content analysis of the connotations revealed seven areas to which they related – nature, values, feelings, people, objects, abstract ideas, and activities. Deeper analyses pointed to the necessity to study the possible influence of other variables (gender, age, value orientation ...) on the understanding of the notion of beauty and its connotations.